(untitled) (Eduscotech, 2023)
This study investigates the effectiveness of WhatsApp as a digital learning platform to enhance students’ speaking skills. Using a qualitative descriptive design, data were collected through observation, interviews, and document analysis. The findings show that WhatsApp supports students’ oral communication through features such as voice notes, video sharing, and chat-based discussions, which provide opportunities for both synchronous and asynchronous speaking practice. The platform helps reduce students’ speaking anxiety, increases participation, and improves fluency as they engage in more flexible and interactive learning activities. Despite challenges related to internet connectivity and potential distractions, WhatsApp remains an accessible and effective mobile-assisted language learning tool when integrated with appropriate teaching strategies. This study highlights the potential of social media platforms in supporting English speaking instruction and provides insights for teachers seeking innovative digital learning approaches.